Input - output framework and economic analysis / Amitabh Kundu...[et al] - Kundu, Amitabh (New Delhi, 1976)
The Centre for the Study of Regional Development of the Jawaharlal Nehru University is involved in the study of the regional dimension of economic phenomena in the country and the interlink ages within them both for diagnostic and prescriptive purposes. Input-output analysis provides an effective tool for identifying the nature, direction and magnitude of such linkages. In the course of our studies, it was soon realized that while there is a great need for developing input-output tables both at the national and regional levels, work done in this sphere is highly inadequate and partial. It is, no doubt, true that the basic schemi of production process has a worldwide applicability. It does not, however, follow from this that a model of interlinkages developed in the U S.A., for example, on the basis of experience in that country can be fruitfully utilized for the analysis of production process in India The task of assimilating the specificities of the national situation in a system of relationships calls for serious intellectural effort, on the one hand, and a clear under standing of the ground to earth realities of production processes, on the other. While there has been an apparent surfeit of the former in Indian scholarship, the latter has been, by and large, conspicuous by its absence. This is particularly true of academia in the universities. Floating in the rarified atmosphere of nebulous model building exercises, there has been a general resistance on its part to "dirty one's hand", so to say, with "mundane" realities. In this process, the development of input output analysis has been a casuality within these ivory towers. It is worth noting in this connection that almost all work in this important field has been done either in research institutes or within the research orbit of the Planning Commission.
Keywords: Interindustry economics- Mathematical models